KINEMATIC ANALYSIS OF LEFT HAND SIDE BLOW TECHNIQUE CONDUCTED BY HIGHLY QUALIFIED ATHLETES SPECIALIZED IN HAND-TO-HAND COMBAT - Vako, I. I.; Zhyrnov, O. V. (Rehabilitation and Recreation, 2023)
The aim of the study is to determine the kinematic features of a left hand side blow technique conducted by highly qualified athletes who specialize in hand-to- hand combat. Research methods. To fulfil the set tasks, research certain methods were used, namely, the analysis of scientific and methodological literature and documentary recourses, methods of registration and analysis of athlete’s movements (system of 3D video registration and analysis of the athlete’s movements “Qualisys Motion Capture”). The results obtained during the research were processed using the methods of mathematical statistics. We registered the technique of performing the studied motor action in 12 highly qualified athletes. The results. The growth of sports results and strengthening of competition on the international sports arena, the rapid development of scientific and technical progress, in particular, the introduction of the latest achievements into sport practice, make it necessary to find new approaches to increase the effectiveness of training and competitive activities of athletes. The use of modern computer technologies allows to create and implement by means of modelling the technique of specific motor actions at the level necessary and sufficient for solving the problems of sports biomechanics. At the same time, it turns out to be possible to effectively and visually set the goal of athletes’ technical training, computer simulation of the proposed option and making appropriate adjustments taking into account the individual characteristics of athlete. A side blow with the help of a left hand from the front stance consists of the same phases as a similar blow performed with the right hand: preparation for the blow; swing; impact movement; contact; return to the starting position. The active phases of impact action last for 0.64 s, or 65.3 % of the total impact duration, the phase of returning to the starting position lasts for 0.34 s, i. e. 34.7 % of the total impact duration. The peculiarities of the time characteristics of the left side blow from the front stance are the relatively long duration of the phase of preparation for the impact (0.3 s) and the quick return to the starting position. The duration of this phase of motor action comprises 0.34 s. Conclusions. In didactic biomechanics, in movement modelling theories, one of the fundamental problems is the transformation of the subjective phenomenon of intention and plan into the objective phenomenon of neuromuscular movement control and learning. It has been established that the side blow with the left hand from the front stance is performed by highly qualified athletes specializing in hand-to- hand combat at a sufficiently high level of efficiency, however, some indicators of the kinematic structure of their blowing technique have certain errors, which somewhat reduce the effectiveness of the blow.